Business intelligence the savvy manager's guide, getting onboard with emerging IT - Loshin, David, 1963- (Amsterdam ; Boston : Morgan Kaufmann Publishers, 2003)
Business Intelligence describes the basic architectural components of a business intelligence environment, ranging from traditional topics such as business process modeling, data modeling, and more modern topics such as business rule systems, data profiling, information compliance and data quality, data warehousing, and data mining. This book progresses through a logical sequence, starting with data model infrastructure, then data preparation, followed by data analysis, integration, knowledge discovery, and finally the actual use of discovered knowledge. The book contains a quick reference guide for business intelligence terminology. Business Intelligence is part of Morgan Kaufmann's Savvy Manager's Guide series. * Provides clear explanations without technical jargon, followed by in-depth descriptions. * Articulates the business value of new technology, while providing relevant introductory technical background. * Contains a handy quick-reference to technologies and terminologies. * Guides managers through developing, administering, or simply understanding business intelligence technology. * Bridges the business-technical gap. * Is Web enhanced. Companion sites to the book and series provide value-added information, links, discussions, and more.
Business intelligence and information exploitation -- The value of business intelligence -- Planning for success -- The business intelligence environment -- Business models and information flow -- Data warehouses, online analytical processing, and metadata -- Business rules -- Data profiling -- Data quality and information compliance -- Information integration -- The value of parallelism -- Alternate information contexts -- Data enhancement -- Knowledge discovery and data mining -- Using publicly available data.
Includes bibliographical references and index.
Keywords: Business intelligence; Information technology -- Management; Management information systems; Electronic books